Internal Innovation Capacity and External Linkages in Firms of ASEAN Economies Focusing on Endogeneity - Masamaru Ogawa; Yasuhi Ueki; Hiroki Idota; Teruyuki Bunno; Masatsugu Tsuji (STI Policy and Management Journal, 2018)
Based on survey data of firms in four ASEAN economies, this paper examines the role of internal innovation capacity which includes technological level, organizational learning, and human resources on innovation. To make this concept more tractable for statistical analysis, an index of internal capacity using AHP (Analytical Hierarchy Process) was constructed. By using this index, this paper attempts to examine how the internal capacity of firms is enhanced by external linkages such as MNCs (Multinational Corporations), universities, and public organizations. In particular, this study analyzes the endogeneity problem, which clarifies the causality between innovation and factors to promote it. In so doing, the instrumental variable method was employed, and as a result, external linkages enhanced internal innovation capacity, and internal innovation capability promotes innovation, while external linkages indirectly enhance innovation.   Key Words- Internal capacity, absorptive capacity, AHP, causality, endogeneity, probit analysis